Promising Practices for Improving Identification of English Learners for Gifted and Talented Programs. (December 2020) - Gubbins, E. Jean; Siegle, Del; Peters, Pamela M.; Carpenter, Ashley Y.; Hamilton, Rashea; McCoach, D. Betsy; Puryear, Jeb S.; Langley, Susan Dulong; Long, Daniel
The underrepresentation of English learners (ELs) in gifted and talented programs is a societal and research problem that merits investigation. Three state departments of education and their state directors of gifted programs supported our access to 16 schools across nine districts. In these three states with gifted identification and programming mandates, ELs were proportionally represented in gifted and talented programs in the 16 schools we visited. Interview data from 225 participants revealed four themes: adopting universal screening procedures, creating alternative pathways to identification, establishing a web of communication, and using professional learning as a lever for change.